Vascular stiffness in insulin resistance and obesity - Jia, Guanghong; Aroor, Annayya R.; DeMarco, Vincent G.; Martinez-Lemus, Luis; Meininger, Gerald A.; Sowers, James R. (Frontiers in Physiology, 2015)
Obesity, insulin resistance, and type 2 diabetes are associated with a substantially increased prevalence of vascular fibrosis and stiffness, with attendant increased risk of cardiovascular and chronic kidney disease. Although the underlying mechanisms and mediators of vascular stiffness are not well understood, accumulating evidence supports the role of metabolic and immune dysregulation related to increased adiposity, activation of the renin angiotensin aldosterone system, reduced bioavailable nitric oxide, increased vascular extracellular matrix (ECM) and ECM remodeling in the pathogenesis of vascular stiffness. This review will give a brief overview of the relationship between obesity, insulin resistance and increased vascular stiffness to provide a contemporary understanding of the proposed underlying mechanisms and potential therapeutic strategies.